In-situ polymerization modified dry method sodium-ion battery prussian blue positive electrode and preparation method and application thereof

CN122889708APending Publication Date: 2026-10-09ZHEJIANG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611334503.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-31
Publication Date
2026-10-09

AI Technical Summary

Benefits of technology

本发明提供一种原位聚合改性的干法钠离子电池普鲁士蓝正极的制备方法,首先在纯干粉的状态下完成普鲁士蓝正极材料、导电剂和聚四氟乙烯粘结剂的混合原纤化,使聚四氟乙烯预先形成承担正极机械骨架作用的三维纤维网络;随后引入聚合物单体、钠盐及引发剂组成的前驱体溶液,使其渗入普鲁士蓝正极材料颗粒和聚四氟乙烯纤维之间,并在后续热压过程中发生原位开环聚合,在干法电极内部形成连续聚合物网络。该聚合物网络与预先原纤化形成的PTFE纤维网络相互贯穿,形成复合支撑结构,在不破坏PTFE干法成型骨架的基础上提高颗粒之间及活性层内部的连接强度,并缓冲普鲁士蓝在Na+嵌入/脱出过程中的局部体积变化和晶格应力。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122889708A_ABST
    Figure CN122889708A_ABST
Patent Text Reader

Abstract

The application relates to the technical field of sodium ion batteries, in particular to a dry-process Prussian blue positive electrode of an in-situ polymerization modified sodium ion battery and a preparation method and application thereof. The preparation method provided by the application firstly completes the mixing and fibrillation of a Prussian blue positive electrode material, a conductive agent and a PTFE binder in a pure dry powder state, so that polytetrafluoroethylene forms a three-dimensional fiber network that bears a positive electrode mechanical skeleton function; subsequently, a precursor solution composed of a polymer monomer, a sodium salt and an initiator is introduced, so that the precursor solution penetrates between Prussian blue positive electrode material particles and polytetrafluoroethylene fibers, and in-situ ring-opening polymerization occurs in a subsequent hot-pressing process, forming a continuous polymer network. The polymer network and the PTFE fiber network formed by fibrillation are mutually penetrated, forming a composite support structure, the connection strength between particles and inside the active layer is improved on the basis of not damaging the PTFE dry-forming skeleton, and the local volume change and lattice stress of Prussian blue in the Na + insertion / extraction process are buffered.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of sodium-ion battery technology, and in particular to an in-situ polymerized modified dry-process Prussian blue cathode for sodium-ion batteries, its preparation method, and its application. Background Technology

[0002] With the rapid development of the new energy and energy storage industries, sodium-ion batteries have become a core technology in the field of large-scale energy storage due to their abundant resources and low cost. To meet the application demands for high energy density and low cost, fabricating thick electrodes with high areal load can reduce the proportion of inactive components, which is an important technical path to improve battery energy density and reduce unit cost.

[0003] Traditional wet-process electrodes are prone to problems such as deterioration of slurry rheology, coating drying cracking, and migration of conductive agents and binders under high areal loading conditions. They also require solvent drying and recycling processes, increasing equipment energy consumption and manufacturing costs. Dry-process electrodes, on the other hand, form a fibrous bonding network through the fibrillation of polytetrafluoroethylene (PTFE). This allows for the formation of high-load, thick electrodes without the use of large amounts of organic solvents, thus offering advantages such as a high proportion of active material, low manufacturing energy consumption, and suitability for thick electrode fabrication.

[0004] However, dry-process thick electrodes still suffer from significant ion transport and structural stability issues. As electrode thickness and areal loading increase, electrolyte wetting and ion transport along the electrode thickness become more difficult. PTFE itself possesses virtually no ion-conducting capacity; its fibrillated network primarily serves a mechanical bonding function, making it difficult to establish continuous and efficient ion transport channels. Therefore, under high-rate charge-discharge conditions, significant Na+ formation is easily observed inside the thick electrode. + Concentration gradients and concentration polarization lead to a decrease in the utilization rate of deep active substances.

[0005] Prussian blue analogues are a class of coordination polymers with a three-dimensional open framework structure. Compared with layered oxides and polyanionic compounds, the core advantage of Prussian blue analogues lies in their excellent balance between cost, rate performance, and theoretical capacity, making them ideal candidate materials for large-scale energy storage applications in sodium-ion batteries. However, the vacancies and water bulk defects in the structure of Prussian blue analogues are superimposed on the intense Jahn-Teller effect and phase transitions during charge and discharge. This causes the bulk problems to spill over to the interface, triggering a series of chain reactions such as electrolyte decomposition and metal dissolution. Summary of the Invention

[0006] The purpose of this invention is to provide a compound that combines the unique structure and interfacial chemical properties of Prussian blue with Na + Prussian blue cathode for sodium-ion batteries with high areal load, enhanced conductivity, structural water regulation, and interface stability.

[0007] This invention provides a method for preparing an in-situ polymerized modified dry-process Prussian blue cathode for sodium-ion batteries, comprising:

[0008] Prussian blue cathode material and conductive agent are mixed evenly, then mixed evenly with PTFE binder, and polytetrafluoroethylene is fully fibrillated to encapsulate the Prussian blue cathode material and the conductive agent to obtain a mixed powder. The polymer monomer, sodium salt and initiator are mixed evenly and prepolymerized to obtain a precursor solution. The mixed powder and the precursor solution are mixed evenly, so that the precursor solution is adsorbed into the gaps between the Prussian blue cathode material and the PTFE binder fibers to obtain the powder. The powder is spread and hot-pressed to obtain a positive electrode film; the positive electrode film is hot-pressed onto the surface of the current collector and then processed to obtain a dry sodium-ion battery positive electrode.

[0009] The initiator initiates the polymerization of polymer monomers to form a polymer network structure between the cathode material, conductive agent, and polytetrafluoroethylene binder.

[0010] Furthermore, the Prussian blue cathode material includes at least one of iron-based Prussian blue, manganese-based Prussian blue, cobalt-based Prussian blue, nickel-based Prussian blue, and copper-based Prussian blue.

[0011] The conductive agent includes at least one of conductive carbon black, Ketjen black (KB), carbon black (CB), graphene, and carbon nanotubes (CNTs).

[0012] Furthermore, the mass ratio of the positive electrode material, the conductive agent, and the polytetrafluoroethylene binder in the mixed powder is 85-94:3-8:1-7.

[0013] Furthermore, the polymer monomer is a cyclic ether monomer.

[0014] After polymerization of cyclic ether monomers, the ether oxygen in the polyether segment can react with Na. + Coordination occurs, forming continuous Na+ between the cathode material particles and PTFE fibers. + This improves the transport path, thereby reducing ion transport resistance and concentration polarization inside the high-area-load dry thick electrode.

[0015] Polyether segments can interact with interstitial water, surface adsorbed water, and some structural water in Prussian blue cathode materials, reducing the tendency of free water to migrate to the electrolyte interface, thereby reducing water-induced electrolyte decomposition and the generation of byproducts such as HF, and reducing the dissolution of Mn in manganese-based Prussian blue and the resulting interface deterioration.

[0016] Furthermore, the cyclic ether monomers include 1,3-dioxolane and 1,1,1-trifluoro-2,3-epoxypropane; the volume ratio of 1,3-dioxolane to 1,1,1-trifluoro-2,3-epoxypropane in the cyclic ether monomers is 0.25-4:1.

[0017] Furthermore, in the precursor solution, the polymer monomer is used as the solvent, and the concentration of the sodium salt is 0.1-1 mol / L; the sodium salt is sodium bis(trifluoromethanesulfonyl)imide (NaTFSI); and the amount of the initiator added is 0.05-0.5 wt% of the polymer monomer mass.

[0018] The initiator is a metal fluorinated methanesulfonate such as aluminum trifluoromethanesulfonate (Al(OTF)3) and stannous trifluoromethanesulfonate (Sn(OTF)2), Lewis acid, or protic acid.

[0019] Fluorine-containing monomers, NaTFSI, and a fluorine-containing initiation system participate in interfacial reactions at the cathode interface, promoting the formation of a stable NaF-containing cathode electrolyte interfacial layer. This interfacial layer, together with the in-situ polymer physical protective layer, reduces the direct contact between the liquid electrolyte and Prussian blue particles, inhibits the continuous oxidative decomposition of the electrolyte and the repeated CEI breakdown and reconstruction, and further reduces Mn dissolution and interfacial impedance growth.

[0020] Furthermore, in the powder, the mass of the precursor solution is 3-8 wt% of the mixed powder.

[0021] Furthermore, the compaction density of the dry-process sodium-ion battery cathode is between 1 and 1.5 g / cc.

[0022] The present invention also provides an in-situ polymerized modified dry sodium-ion battery Prussian blue cathode, which is prepared by the preparation method described above.

[0023] The present invention also provides a sodium-ion battery, comprising a positive electrode, a negative electrode, a separator, and an electrolyte as described above.

[0024] In summary, the advantages and beneficial effects of the present invention are as follows: This invention provides a method for preparing a dry-process sodium-ion battery Prussian blue cathode material modified by in-situ polymerization. First, Prussian blue cathode material, a conductive agent, and a polytetrafluoroethylene (PTFE) binder are mixed and fibrillated in a pure dry powder state, allowing the PTFE to pre-form a three-dimensional fiber network that serves as the mechanical framework of the cathode. Then, a precursor solution composed of polymer monomers, sodium salt, and an initiator is introduced, allowing it to penetrate between the Prussian blue cathode material particles and the PTFE fibers. In-situ ring-opening polymerization occurs during subsequent hot pressing, forming a continuous polymer network inside the dry-process electrode. This polymer network interpenetrates with the pre-fibrillated PTFE fiber network, forming a composite support structure. This improves the connection strength between particles and within the active layer without damaging the PTFE dry-process framework, and buffers the Prussian blue in the Na+. + Local volume changes and lattice stress during the insertion / extraction process. Attached Figure Description

[0025] Figure 1 The graph shows the rate performance test results of the battery assembled in Example 1 of this invention. Figure 2 The graph shows the rate performance test results of the battery assembled in Comparative Example 1 in this invention. Figure 3 This is a graph showing the cycle stability test results of the battery assembled in Example 1 of this invention at 3C. Figure 4 The graph shows the cycle stability test results of the battery assembled in Comparative Example 1 of this invention at 3C. Figure 5 The XRD patterns are of the active materials of the positive electrodes prepared in Example 1 and Comparative Example 1 of this invention. Figure 6 This is a SEM image of the active material of the positive electrode prepared in Example 1 of this invention and the fluorinated polydioxolane copolymer (PFDOL); Figure 7 These are FTIR images of the precursor solution prepared in Example 1 of this invention before and after polymerization; Figure 8 This is a CV curve of the battery assembled in Example 1 of the present invention; Figure 9 This is a CV curve of the battery assembled in Comparative Example 1 of this invention. Detailed Implementation

[0026] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions of this invention will be clearly and completely described below in conjunction with specific embodiments and corresponding drawings. Obviously, the described embodiments are only a part of the embodiments of this invention, and not all of them. Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this invention.

[0027] Example 1 The specific steps for preparing an in-situ polymerized modified Prussian blue cathode for dry-process sodium-ion batteries are as follows: Step 1: Preparation of mixed powder The Prussian blue cathode material uses commercially available manganese-iron-based Prussian blue (PB). The conductive agent is Ketjen Black. The binder is polytetrafluoroethylene (PTFE) powder. The mass ratio of manganese-iron-based Prussian blue, conductive agent, and PTFE binder is 92.5:3:4.5. The manganese-iron-based Prussian blue and conductive agent are pre-mixed in a high-speed disperser at a paddle linear speed of 20 m / s for 30 min to ensure the conductive agent uniformly coats the surface of the active material particles. Then, the PTFE binder is added, and mixing continues for another 30 min to fully fibrillate the PTFE and construct a three-dimensional fiber bonding network, encapsulating the manganese-iron-based Prussian blue and conductive agent particles to obtain a mixed powder.

[0028] Step 2: Prepare the precursor solution 1,3-Dioxolane (DOL) and 1,1,1-trifluoro-2,3-epoxypropane were used as monomers, with a volume ratio of 4:1, and served as solvents. Sodium bis(trifluoromethanesulfonyl)imide (NaTFSI) was used as the sodium salt electrolyte. A 0.1 mol / L NaTFSI solution was prepared in an argon-atmosphere glove box and magnetically stirred until completely dissolved. Then, 0.5 wt% Al(OTF)3 initiator (relative to monomer mass) was added and stirred for 3 min to obtain a homogeneous and transparent solution. The prepared solution was sealed and placed in a 60 °C environment for prepolymerization for 30 min to obtain the precursor solution.

[0029] Step 3: Blend the mixed powder and precursor solution A precursor solution accounting for 5 wt% of the mass of the mixed powder is added to the mixed powder. Under low-speed stirring conditions, the precursor solution is uniformly adsorbed on the surface of the manganese iron-based Prussian blue particles and in the gaps between the PTFE fibers to obtain a composite electrode powder in the form of thin sheets.

[0030] Step 4: Preparation of self-standing electrode film by hot roller thinning The powder is evenly spread and rolled into shape using a differential speed roller press at 80°C. The roller gap and roller pressure are adjusted according to the target surface load to prepare a self-supporting dry cathode membrane.

[0031] Step 5: Composite current collector and post-drying treatment The positive electrode film was hot-pressed onto the surface of the carbon-coated aluminum foil current collector at 100 °C, and the thickness was reduced to control the areal loading at 25 mg / cm². 2 The compacted density is approximately 1.2 g / cc. It is then punched into circular electrode sheets with a diameter of 10 mm; the electrode sheets are placed in a vacuum oven and vacuum dried overnight at 80°C to remove residual unreacted monomers and trace amounts of moisture, thus obtaining the modified positive electrode sheet.

[0032] Example 2 The difference between this embodiment and Embodiment 1 is that in step 3, a precursor solution accounting for 3 wt% of the mass of the mixed powder is added to the mixed powder.

[0033] Example 3 The difference between this embodiment and Embodiment 1 is that in step 2, all the polymer monomers added are 1,3-dioxolane (DOL).

[0034] Comparative Example 1 The difference between this comparative example and Example 1 is that no precursor solution is added.

[0035] The specific steps for preparing an in-situ polymerized modified dry-process sodium-ion battery cathode are as follows: Step 1: Preparation of mixed powder Prussian blue cathode material is made of PB. Ketjen black is used as the conductive agent. PTFE powder is used as the binder. The mass ratio of manganese-iron-based Prussian blue, conductive agent, and PTFE binder is 92.5:3:4.5. The manganese-iron-based Prussian blue and conductive agent are pre-mixed in a high-speed disperser at a paddle linear speed of 20 m / s for 30 min to ensure the conductive agent uniformly coats the surface of the active material particles. Then, the PTFE binder is added, and mixing continues for another 30 min to fully fibrillate the PTFE and construct a three-dimensional fiber bonding network, encapsulating the manganese-iron-based Prussian blue and conductive agent particles to obtain a mixed powder.

[0036] Step 2: Preparation of self-standing electrode film by hot roller thinning The mixed powder is evenly spread and rolled into shape using a differential speed roller press under heating conditions of 80°C. The roller gap and roller pressure are adjusted according to the target surface load to prepare a self-supporting dry cathode membrane.

[0037] Step 5: Composite current collector and post-drying treatment The positive electrode film was hot-pressed onto the surface of the carbon-coated aluminum foil current collector at 100 °C, and the thickness was reduced to control the areal loading at 25 mg / cm². 2 The compacted density was approximately 1.2 g / cc. It was then punched into circular electrode sheets with a diameter of 10 mm; the electrode sheets were placed in a vacuum oven and vacuum dried overnight at 80 ℃ to remove trace amounts of moisture, yielding the modified positive electrode sheet.

[0038] Button battery assembly method: The battery was assembled in a glove box with a water and oxygen content of <0.1 ppm. The negative electrode was made of sodium metal with a diameter of 15.6 mm, the separator was made of glass fiber, and the electrolyte was NC-139 type electrolyte. The positive electrodes obtained in the examples and comparisons were assembled into CR2025 type button batteries. After assembly, the batteries were allowed to stand for 12 hours to ensure that the electrolyte was fully immersed before battery performance testing.

[0039] Performance testing: The batteries assembled from Examples 1-3 and Comparative Example 1 were tested, and the specific test items are as follows.

[0040] 1. The rate performance of the batteries assembled in Example 1 and Comparative Example 1 at 0.1 C, 0.5 C, 1 C, 2 C, 3 C, 4 C, and 5 C was tested at 25 °C. The charge-discharge performance of the batteries assembled in Example 2 and Example 3 at 0.1 C was also tested. The positive electrode areal loading of Examples 1-3 and Comparative Example 1 was 25 mg / cm³. 2 The theoretical specific capacity at 1C is 170 mA g. -1 The test results are as follows: Figures 1-2 As shown in Table 1.

[0041] Table 1 Test Results

[0042] like Figures 1-2 As shown, the discharge specific capacity of Example 1 at 0.1 C is 149.35 mAh g. -1 The comparative example 1 was 143.09 mAh g. -1 As shown in Table 1, the discharge specific capacity of Example 2 at 0.1 C is 145.48 mAh g. -1 Example 3 is 147.72 mAh g -1Compared to Examples 2, 3, and Comparative Example 1, Example 1 exhibits a more fully utilized capacity and higher utilization rate of active material at 0.1 C. It can be seen that at different current densities, the discharge specific capacity of Example 1 is higher than that of Comparative Example 1. This indicates that Example 1 achieves a more fully utilized capacity under high current, and the in-situ polymerization modification constructs an ion conduction network within the electrode structure, reducing ion transport resistance.

[0043] 2. The cycle stability of the batteries assembled in Example 1 and Comparative Example 1 was tested at 3C. All batteries were activated at 0.1C for 3 cycles, and then cycled 50 times at 3C. The test results are as follows: Figures 3-4 As shown.

[0044] like Figures 3-4 As shown, Example 1 maintained a capacity retention of 81.5% after 50 cycles at 3 C, while Comparative Example 1 only maintained 46.1%. This indicates that the conductive network of the fluorinated polydioxolane copolymer (PFDOL) formed by in-situ polymerization, on the one hand, constructs a physical barrier layer on the particle surface and a NaF-rich positive electrode electrolyte interface phase CEI film, effectively inhibiting Mn dissolution and continuous electrolyte decomposition; on the other hand, the flexible polymer network buffers Mn. 3+ The Jahn-Teller anisotropic stress reduces the pulverization of cathode material particles and electrical contact failure, thereby significantly improving the cycle life of dry-process thick electrodes at high rates.

[0045] 3. Cut small pieces with a diameter of 10 mm from the positive electrode sheets of Example 1 and Comparative Example 1, respectively. Fix the electrode sheets flat on the XRD sample stage, ensuring the test surface is level and without significant warping. Then, perform XRD testing directly on the active material layer of the electrode sheets. The test uses a Cu Kα radiation source (λ = 1.5406 Å), with a scanning range of 10°–80°, a scanning step size of 0.02°, and a scanning speed of 2. o / min, the test results are as follows Figure 5 As shown.

[0046] like Figure 5 As shown, the XRD detection results of Comparative Example 1 and Comparative Example 1 show that after introducing PFDOL into the cathode, the positions of the characteristic diffraction peaks of PB did not shift significantly, and the peak shape and relative intensity remained basically consistent. This indicates that the addition of PFDOL formed by in-situ polymerization did not change the cell parameters and lattice structure of PB, and did not damage the crystallinity of PB.

[0047] 4. After cutting the positive electrode sheet from Example 1, fix it flat onto the conductive adhesive and place it on the sample stage of a scanning electron microscope, ensuring that the test surface is horizontal and without obvious warping. Observe the microstructure of the electrode surface using a scanning electron microscope (SEM), with a test accelerating voltage of 20 kV and a working distance of 7.0 mm.

[0048] like Figure 6 As shown, the positive electrode sheet of Example 1 was characterized by SEM. The SEM morphology is as follows. Figure 6 As shown, the thin film structure that coats the surface of the active material particles and fills the gaps between the particles is PFDOL generated by in-situ polymerization.

[0049] 5. The samples before and after polymerization were characterized using a Thermo Scientific Nicolet iS20 Fourier transform infrared spectrometer. To verify the polymerization behavior of FDOL monomer, a precursor solution was prepared for polymerization verification. Specifically, in an argon-atmospheric glove box, 1,3-dioxolane (DOL) and 1,1,1-trifluoro-2,3-epoxypropane were mixed at a volume ratio of 4:1, and 0.1 mol / L sodium bis(trifluoromethanesulfonyl)imide (NaTFSI) was added. The mixture was magnetically stirred until completely dissolved. The solution was divided into two portions: one portion was used as the monomer sample before polymerization (FDOL), and the other portion was mixed with 0.5 wt% Al(OTF)3 initiator relative to the monomer mass. The mixture was stirred for 3 min to obtain a homogeneous and transparent solution. After thorough mixing, the solution was sealed and polymerized at 60℃ for 1 h to obtain the polymer sample after polymerization (PFDOL). Both samples were subjected to ATR-FTIR testing at a resolution of 4 cm⁻¹. -1 32 scans, wavenumber range 4000-500cm -1 The test results are as follows: Figure 7 As shown.

[0050] The FDOL monomer before polymerization was at 1156.5 cm⁻¹ -1 and 663.2 cm -1 It exhibits a characteristic absorption peak containing fluorine groups at 913.2 cm⁻¹, and also shows a peak at 913.2 cm⁻¹. -1 The presence of characteristic vibrational peaks of cyclic structural units indicates that the monomer simultaneously possesses fluorinated segments and polymerizable cyclic reactive groups.

[0051] The infrared spectrum of PFDOL obtained after in-situ polymerization shows that the original monomer contains 913.2 cm⁻¹ -1 The complete disappearance of the characteristic peak of the cyclic structure at 1171.4 cm⁻¹ indicates that the reactive groups have fully participated in the polymerization; the characteristic absorption peak of the fluorine-containing group is at 1171.4 cm⁻¹. -1 and 631.9cm -1 The presence of this feature indicates that the fluorinated structural units were retained during the polymerization process; furthermore, 846.8 cm -1 A new characteristic absorption peak appeared, corresponding to the formation of the long polymer chain structure. This proves the successful polymerization of the fluoropolymer PFDOL.

[0052] 6. The batteries assembled in Example 1 and Comparative Example 1 were subjected to cyclic voltammetry (CV) testing, and the CV curves for the first three cycles were obtained at a scan rate of 0.1 mV / s. Figure 8 This is the CV curve diagram of the first three cycles of Example 1. Figure 9 This is the CV curve of the first three cycles of Comparative Example 1.

[0053] like Figures 8-9 As shown, the process from low potential to high potential is an oxidation process, with Fe at low potential being the oxidation process. 2+ / Fe 3+ The oxidation peaks, with the high potential being Mn 2+ / Mn 3+ The oxidation peak; the reduction process occurs from high potential to low potential, with the peak at high potential being Mn. 3+ / Mn 2+ The reduction peak at low potential is Fe. 3+ / Fe 2+ The reduction peak of Mn. 3+ / Mn 2+ The potential difference between the oxidation and reduction peaks was measured in the following ways: In the first cycle, Example 1 had a potential difference of 0.330 V, while Comparative Example 1 had a potential difference of 0.359 V; in the second cycle, Example 1 had a potential difference of 0.269 V, while Comparative Example 1 had a potential difference of 0.281 V; and in the third cycle, Example 1 had a potential difference of 0.260 V, while Comparative Example 1 had a potential difference of 0.273 V. Comparing the potential differences shows that Example 1 exhibits less polarization and better overlap across different cycles, indicating that Example 1 has better cycle reversibility compared to Comparative Example 1.

[0054] Compared to Comparative Example 1, Example 1 exhibits a discharge specific capacity of 149.35 mAh g at 0.1 C. -1 The comparative example 1 was 143.09 mAh g. -1 In Example 1, the discharge specific capacity at 3 C remained at 109.39 mAh g⁻¹. -1 The discharge specific capacity of Comparative Example 1 was 91.56 mAh g. -1 The discharge specific capacity at 5 C remains at 34.48 mAh g. -1 The discharge specific capacity of Comparative Example 1 is 16.77 mAh g. -1 To address the issues of long ion diffusion paths, high transport resistance, and severe polarization at high rates caused by dense pores and uneven electrolyte wetting in dry-process electrodes, the in-situ generated 1,3-dioxolane-based polymer network can construct continuous three-dimensional ion conduction channels between particles and within pores. This effectively reduces the ion transport impedance and concentration polarization of the electrode, compensates for the shortcomings of ion conduction in the dry-process system, and significantly improves the utilization rate and rate performance of active materials under high-current charge and discharge.

[0055] Compared to Comparative Example 1, Example 1 maintained a capacity retention of 81.5% after 50 cycles at 3 C, while Comparative Example 1 only maintained 46.1%. This demonstrates that, addressing the issues of PTFE binder fibers being prone to breakage and collapse, conductive network failure, and rapid capacity decay under repeated volume deformation of the active material, the in-situ polymer network can form an interpenetrating composite support system with the PTFE fibers, buffering the volume expansion and contraction of the material and maintaining the integrity of the electrode structure and conductive network. Simultaneously, it forms a uniform coating layer on the surface of the active material, stabilizing the electrode interface and mitigating capacity decay, thus improving long-cycle stability from both structural and interface dimensions.

[0056] Furthermore, this invention employs a fluorinated initiation system composed of 1,1,1-trifluoro-2,3-epoxypropane monomer, sodium bis(trifluoromethanesulfonyl)imide (NaTFSI), and initiator Al(OTF)3. The PFDOL polymer layer formed by in-situ polymerization uniformly covers the surface of the active material particles. On one hand, it acts as a physical barrier, reducing direct contact between the liquid electrolyte and the positive electrode active material, inhibiting the continuous oxidative decomposition of the carbonate solvent at high potentials, and preventing repeated thickening and reconstruction of the CEI (positive electrode electrolyte interface). On the other hand, the TFSI dissolved in the polymer network... - During the first charge, fluorine-containing anions undergo oxidative decomposition at the positive electrode interface, promoting the formation of a thin, dense, and stable CEI rich in NaF inorganic components on the particle surface. NaF exhibits high chemical stability and a wide electrochemical window, effectively blocking Mn. 2+ It dissolves and resists HF corrosion. Simultaneously, the PFDOL polyether chain is rich in ether oxygen bonds (-COC-), which can interact with interstitial water and surface adsorbed water in the Prussian blue structure through hydrogen bonding. This helps to bind water molecules within the polymer network, reducing the migration of free water into the electrolyte, thereby inhibiting the reaction of water with the electrolyte to generate HF and the resulting interfacial side reactions. The structural water anchored in the network can also continue to function as a lattice support and buffer Na+. + The role of volume change during the intercalation / deintercalation process is to reduce irreversible structural phase transitions caused by excessive loss of water of crystallization.

[0057] Finally, it should be noted that any modification or equivalent substitution of some or all of the technical features made based on the technical solutions of this invention and the embodiments thereof, without departing from the corresponding technical solutions of this invention, shall fall within the patent scope of this invention and the embodiments thereof.

Claims

1. A method for preparing an in-situ polymerized modified dry-process Prussian blue cathode for sodium-ion batteries, characterized in that, include: Prussian blue cathode material and conductive agent are mixed evenly, then mixed evenly with polytetrafluoroethylene binder, and polytetrafluoroethylene is fully fibrillated to encapsulate the Prussian blue cathode material and the conductive agent to obtain a mixed powder. The polymer monomer, sodium salt and initiator are mixed evenly and prepolymerized to obtain a precursor solution. The mixed powder and the precursor solution are mixed evenly, so that the precursor solution is adsorbed into the gaps between the Prussian blue cathode material and the polytetrafluoroethylene binder fibers to obtain the powder. The powder is spread and hot-pressed to obtain a positive electrode film; the positive electrode film is hot-pressed onto the surface of the current collector and then processed to obtain a dry sodium-ion battery positive electrode.

2. The preparation method according to claim 1, characterized in that, The Prussian blue cathode material includes at least one of iron-based Prussian blue, manganese-based Prussian blue, cobalt-based Prussian blue, nickel-based Prussian blue, and copper-based Prussian blue.

3. The preparation method according to claim 1, characterized in that, The mass ratio of the positive electrode material, the conductive agent, and the polytetrafluoroethylene binder in the mixed powder is 85-94:3-8:1-7.

4. The preparation method according to claim 1, characterized in that, The polymer monomer is a cyclic ether monomer.

5. The preparation method according to claim 4, characterized in that, The cyclic ether monomers include 1,3-dioxolane and 1,1,1-trifluoro-2,3-epoxypropane; the volume ratio of 1,3-dioxolane to 1,1,1-trifluoro-2,3-epoxypropane in the cyclic ether monomers is 0.25-4:

1.

6. The preparation method according to claim 5, characterized in that, In the precursor solution, the polymer monomer is used as the solvent, and the concentration of the sodium salt is 0.1-1 mol / L; the sodium salt is sodium bis(trifluoromethanesulfonyl)imide; the amount of the initiator added is 0.05-0.5 wt% of the polymer monomer mass.

7. The preparation method according to claim 1, characterized in that, In the powder, the mass of the precursor solution is 3-8 wt% of the mixed powder.

8. The preparation method according to claim 1, characterized in that, The compaction density of the dry-process sodium-ion battery cathode is between 1 and 1.5 g / cc.

9. A dry-process Prussian blue cathode for sodium-ion batteries, modified by in-situ polymerization, characterized in that, It is prepared by the preparation method according to any one of claims 1-8.

10. A sodium-ion battery, characterized in that, It includes the positive electrode, negative electrode, membrane, and electrolyte as described in claim 9.